Memayu Hayuning Sasama sebagai Falsafah Hidup Masyarakat Desa Multireligius Buntu Wonosobo dalam Perspektif Dakwah Humanis Dan Living Hadis - fajriatul mustakharoh; khusnul khotimah; ahmad hidayatullah (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2025)
This article discusses the implementation of the Memayu Hayuning Sasama philosophy in the lives of the people of Buntu Village, Wonosobo, as a model of multireligious harmony from the perspective of humanist da'wah and living hadith. Using a qualitative research approach with a phenomenological perspective, the study found that Buntu Village demonstrates how people of different religions can coexist peacefully while upholding the values of tolerance, brotherhood, and social justice. The humanist da'wah approach in this village emphasizes respect for human rights, dialogue, and empathy, reflecting Islam's inclusive values and rejection of sectarianism. Meanwhile, through the study of living hadith, this research also explores how the hadith of Prophet Muhammad is implemented in the social life of Buntu's community, particularly in fostering harmonious interfaith interactions. The Muslim majority exhibits openness by embracing minority communities in various aspects of life, including leadership roles and strategic positions within the village administration.